Protective effect of Lifor solution in experimental renal ischemia-reperfusion injury - Regner, Kevin R. (2010)
BACKGROUND: Improved kidney preservation methods are needed to reduce ischemia-reperfusion (IR) injury in kidney allografts. Lifor is an artificial preservation solution comprised of nutrients, growth factors, and a non-protein oxygen and nutrient carrier. The current study compared the effectiveness of Lifor to University of Wisconsin solution (UW) in protecting rat kidneys from warm IR and cold storage injury. MATERIALS AND METHODS: In a warm IR model, rat kidneys were perfused in situ with either saline, UW, or Lifor for 45 minutes. Renal function and histology were assessed 24 hours later. In a cold IR model, kidney slices were cold stored in saline, UW, or Lifor at 4°C. Kidney injury was assessed by the release of lactate dehydrogenase (LDH) and immunoblot analysis for cleaved caspase-3. RESULTS: Lifor perfusion significantly mitigated renal dysfunction and tubular injury at 24 hours compared to saline or UW. Lifor and UW prevented LDH release in hypoxic kidney slices in vitro, however activation of caspase-3 following hypoxia-reoxygenation was attenuated only with Lifor. Cold storage with Lifor or UW significantly decreased LDH release from kidney slices or normal rat kidney cells in comparison to storage in saline or culture media. After 24 hours of cold storage there was a significant decrease in cleaved caspase-3 in Lifor stored slices compared that seen following cold storage in saline or UW solution. CONCLUSIONS: Lifor solution mitigates both warm and cold renal IR and appears to provide greater protection from apoptosis as compared to UW solution.